Opportunities and Challenges of Community Participation in Community-Based Ecotourism Development in Wof-Washa Forest Area - Shewandagne Alemayehu Dubale; Berhanu Esubalew (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2024)
The involvement of the community is the lifeblood to Community-Based Ecotourism (CBET) development in the destination. The study focused on investigate opportunities and challenges to community participation in the development of the Ecotourism. The study employed descriptive design with mixed approach via cross-sectional survey. The target population were community members and tourism experts. It used systematic, stratified, and purposeful sampling methods. Primary data collected via questionnaires, interview, structured observation, and secondary data by document review. The analysis method was thematic for qualitative, and descriptive statistics for quantitative data. The study indicated communities are motivated to participate in ecotourism development due to income, employment, infrastructure, and cultural revitalization benefits. However, unfair distribution of benefits, HWC (Human-wildlife conflicts), shortage of skilled manpower, and absence of coordination among stakeholders are hampered their involvement. Generally, the participation of community stimulated by opportunities, but limited by bottleneck factors. The author recommend that all stakeholders should be working in collaborative way to reduced obstacles by improving motivator elements of community participation for develop an impactful community-based ecotourism project in Wof-Washa National Priority Forest Area.